Pharmacokinetics and Biodistribution of Eriocitrin in Rats - Ferreira, Paula S. [UNESP]; Manthey, John A.; Nery, Marina S. [UNESP]; Cesar, Thais B. [UNESP] (American Chemical Society (ACS), 2021)
Eriocitrin plays a role in the reduction of oxidative stress and inflammation linked to the development of diabetes mellitus and atherosclerosis. We investigated the pharmacokinetics and distribution of eriocitrin metabolites in rats orally administered with eriocitrin. Plasma, urine, and organs were collected at 12 different time points from 0 to 24 h and analyzed by HPLC-PDA-MS. For the first time, the metabolism and distribution of orally administered eriocitrin were shown. Nine metabolites of eriocitrin were identified in rat urine, and seven in various tissues (eriodictyol, homoeriodictyol, hesperetin, and glucuronidated metabolites), and preliminary identifications of these metabolites are suggested. Overall, eriocitrin metabolites were widely distributed in the rat tissues, where homoeriodictyol and homoeriodictyol-7-O-glucuronide were the major metabolites. The half-lives of the metabolites in plasma were between 3 and 3.2 h, and the total bioavailability of eriocitrin was less than 1%.
Keywords: biodistribution; eriocitrin; identification; metabolites; pharmacokinetics